Representation of the “fire” concept in Russian language picture of the world - Fatimat V. Shogenova (Кавказология)
The article investigates the characteristics of the representation of the notion "Fire" in the Russian linguistic vision of the world. Fire is an essential component of civilization and one of the fundamental concepts that holds universal worth. Scientific novelty lies in the detailed linguacultural and cognitive-discursive analysis of figurative units (metaphors, proverbs, sayings, phraseological units, etc.), which act as the main components-constructs of the concept “Fire” as a fragment of the Russian linguistic picture of the world. As a result of the analysis of the empirical material, significant conceptual features of the mental formation “Fire”, value components that form its core, central and peripheral zones are identified. The article uses Kabardian figurative units representing this concept as background material, which allows us to see the important role of this concept in the consciousness of native speakers, and also makes it possible to highlight the features of the linguistic picture of the world of both ethnic groups.